Inmediacy, hypermediation, remediation - Bolter, David Jay; Grusin, Richard (CIC. Cuadernos de Información y Comunicación, 2011)
The authors review some concepts of media analysis such as hypermediacy, inmediacy, adding the original concept of re-mediation to define the form-retrieving processes of representation in new media that appear when a new technology of communication is born. The three processes: immediacy, hypermediacy and re-mediation, constitute formal evolutions with dynamics of a defined nature in each case, that could help us to understand the technological processes and their cultural action.